2009
DOI: 10.4049/jimmunol.0901865
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FcεRI Expression during Murine Basophil Maturation: The Interplay between IgE, Cell Division, and FcεRI Synthetic Rate

Abstract: Expression of FcεRI on basophils and mast cells is modulated by IgE Ab. Previous studies have noted in vivo receptor expression dynamics that are discordant with expectations derived from in vitro studies. The current study presents a formal hypothesis to explain the discordant observations and tests two assumptions that underlie a proposed model of receptor dynamics. After first showing that a murine model of receptor expression on basophils recapitulates observations made using human basophils, the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There is increasing evidence that changes observed in vitro may be blunted relative to changes that can occur in vivo . For example, synthesis of FcεRIα is markedly blunted in vitro , perhaps by 20 fold [ 46 , 47 ]. Likewise, synthesis of FcRβ is nearly non-existent in vitro [ 48 ], even with IL-3 present, but is clearly present in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that changes observed in vitro may be blunted relative to changes that can occur in vivo . For example, synthesis of FcεRIα is markedly blunted in vitro , perhaps by 20 fold [ 46 , 47 ]. Likewise, synthesis of FcRβ is nearly non-existent in vitro [ 48 ], even with IL-3 present, but is clearly present in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that only a limited number of unoccupied receptors exist on the surface of basophils and mast cells. Although quantifying the numbers of unoccupied receptors is difficult (39), it was clear that both basophils and mast cells had sufficient unoccupied receptors to bind exogenous IgE (Figure 2). Indeed, the regulation of surface FcεRI is thought to occur mainly through stabilization of unoccupied receptors after IgE binding with a dynamic balance between de novo IgE production and endocytosis of unoccupied receptors (40).…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by our results showing that during Nb infection, basophils cannot be identified via anti-FcεRI (Fig. 3A, [14,17]) because the FcεRI receptor accessibility is blocked by high IgE concentration in the serum [36]. Our analysis of sorted CD41 int CD45 int cells showed that they display almost exclusively basophil morphology from our cytospin experiments.…”
Section: Discussionmentioning
confidence: 57%
“…This is evidenced by our results showing that during Nb infection, basophils cannot be identified via anti‐FcεRI (Fig. A, ) because the FcεRI receptor accessibility is blocked by high IgE concentration in the serum .…”
Section: Discussionmentioning
confidence: 80%